Engaging students in critical thinking through information competency assessment: A single group repeated measures design / Lleuvelyn Areglado Cacha - Lleuvelyn, Areglado Cacha (2013)

(untitled)
This study investigated the extent to which critical thinking could be promoted through question based framework via information competency assessment. The ability to evaluate information’s credibility using critical thinking is key indicator of information competency. The study set out to determine strategies how critical thinking transpired through infusion of information competency into content instructions to encourage critical thought processes and authentic learning. An assessment tool is required where students are empowered to challenge ideas, investigate complex information problems, and look for workable solutions integrating information technology capabilities. Prior to commencing the study, a range of online assessment tools used in universities abroad including iSkills and iCritical Thinking Certification of ETS are reviewed to gain insights into best instructive practices that encourage critical thinking in research, evaluation, creation and communication of information. Using questioning or problem-based approach in the constructivist and cognitive framework the study has established that technology integration supports higherlevel cognitive processes as it increases student’s effective interaction with information. A repeated measures design is used with pre-test/post-test and investigative searching assessment to determine the degree of learning and evidence of critical thinking skills resulting from the web based assessment of information competency. The design manipulates the impact of instructional strategies for furthering critical thinking through active engagement with problem solving exercises in steady progression of information competency skills. Initial sample consisted 21 Masters of Library and Information Science graduate students, of whom 3 did not complete, with strongly varying academic backgrounds, professional experience and with different levels of competence participated in this study. The practical relevance of using repeated measures design, employing the same group of participants in every assessment is clearly supported by the current findings. It makes sense to get information from a single group of graduate students through multiple benchmark assessments across a five-month semester course “Information Needs and Behaviour”. Students’ intense participation in multiple cognitive skills assessment activities allows researcher to check perspectives that facilitate understanding through descriptive qualitative strategies. Utilizing the strategy of supplementing quant itative with qualitative methods lessens perceptibly the amount of time it takes to collect multiple-data in different ways to describe accurately the phenomenon under study. Quantitative data included scores through repeated measures design of pretest/posttest, and a foreign based investigative searching assessment. While qualitative data utilized descriptive means, open-ended questions, interviews to capture participants’ perceived challenges and learning experience further evidenced from student learning portfolios to verify improvement of their critical thinking. The results corroborated with participants’ responses that purposeful assessment activities that involved well thought out evaluation of information’s credibility and significance can increase their cognitive abilities to problem solve and make informed decisions regardless of their starting point or aptitude level. Findings signified that individual students can make an amount of improvement through active learning engagement on tasks that trigger further inquiry and careful evaluation that sharpen critical thinking. Finally, the study has given an account that web based assessment of information competency can be an invaluable tool for encouraging critical thinking as evidenced by assessment results and participants’ responses. It provides the means to practice and increase awareness of their critical thinking to improve the outcomes of their thought processes